Formal Methods for Dynamical Systems 13th International School on Formal Methods for the Design of Computer, Communication, and Software Systems, SFM 2013, Bertinoro, Italy, June 17-22, 2013. Advanced Lectures - Bernardo, Marco; de Vink, Erik; Di Pierro, Alessandra; Wiklicky, Herbert (Programming and Software Engineering, 2013)
This book presents 5 tutorial lectures given by leading researchers at the 13th edition of the International School on Formal Methods for the Design of Computer, Communication and Software Systems, SFM 2013, held in Bertinoro, Italy, in June 2013. SFM 2013 was devoted to dynamical systems and covered several topics including chaotic dynamics; information theory; systems biology; hybrid systems; quantum computing; and automata-based models and model checking.